Phosphate nephropathy after administration of bowel purgative containing sodium phosphate – a case report - Perkowska-Ptasińska, Agnieszka; Szewczyk, Katarzyna; Skuza, Anna; Wasińska-Krawczyk, Anna; Rydzewski, Andrzej (Polish Journal of Pathology, 2014)
A 65-year-old woman was admitted to the hospital with an elevated serum creatinine concentration associated with leukocyturia and erythrocyturia. Past medical history analysis revealed that four months before current hospitalization she had been subjected to colonoscopy preceded by the administration of oral sodium phosphate solution (OSP) as preparation for this procedure. Kidney biopsy revealed mild chronic tubulo-interstitial inflammation and scarring with prominent cortical tubular calcium phosphate deposits. The diagnosis of phosphate nephropathy, most probably secondary to OSP ingestion was made. During follow-up the renal function remained impaired but stable with eGFR of 25 ml/min/1.73 m². The patient is currently under the care of the nephrology clinic.